Conyers Place and the problem of reliability of reason - Drozdek, Adam (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
Conyers Place was an eighteenth-century Anglican author who adamantly defended the priority of revelation in theological matters. To that end, he argued at length how unreliable human reason is and thus how inadmissible is natural theology; however, through his work he indicated that reason can be used quite effectively in the service of theology when its arguments are based on revelation, which he showed in his sometimes sophisticated, imaginative, if not infrequently controversial discussion of the problem of space, light, and panpsychism.